The EMK and Iraultza, «two-way path» (1891-1991) - García Lerma, Miguel; Aparicio Rodríguez, Víctor (Huarte de San Juan. Geografía e Historia, 2018)
This article seeks to make an approach and analysis of the organization Iraultza, from its origins to its disappearance in the early 1990s. Our methodological approach is based on documentary and hemerographic analysis, and the use of oral sources as a tool that allows us to draw some of these difficulties derived from the inaccessibility of the internal documentation of the organization. This combination of techniques allows us to analyze the genesis of the organization and the principles that will be articulated during its existence, as well as its impact on the Basque-Navarre context in the eighties. Iraultza will be born from the strategic shift that since the late seventies occurs in the mc-emk, which will approach the radical Basque nationalism in order to defend a rupturist project, giving rise to the emergence of a group inspired by the debates of the groups armed of the moment.